Legal Groundwork for Preventing Religious Extremism in the Kazakhstan Republic - RAIBYAEV, Daulet Kumarbekovich (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
In the presented article a legal framework for the countermeasures against religious extremism in the Kazakhstan Republic are investigated. The legal norms of the laws of the Kazakhstan Republic, which regulate the application of the countermeasures against religious extremism, the court practice, the statistic data, reflecting the results of the legal norms application have been studied. The role of the country's leadership, especially the President of the Kazakhstan Republic Nursultan Nazarbayev in the development, implementation and improvement of the public policy of fight against religious extremism is emphasized. While studying the foreign approaches, the authors suggest to formalize in law the status of a traditional religious organization, assuming, that thereby one could join the efforts of the state and the clergy in preventing the spread of religious extremism. Some proposals for developing the cooperation between the state and the clergy in this area have been made.
Keywords: religious extremism, radical religious sects, religious organization, traditional religion